2022
DOI: 10.1109/access.2022.3170068
|View full text |Cite
|
Sign up to set email alerts
|

A Big Data Analysis on Urban Mobility: Case of Bangkok

Abstract: Designing an efficient on-demand mobility service requires comprehensive knowledge on the statistical characteristics of trips. In other words, it is critical to know how long passengers typically spend on a trip and how far they usually travel. Likewise, it is important to learn how much time a driver spends searching for passengers. This study presents a statistical analysis of taxi trips in Bangkok based on real traces of 5,853 taxis over the period of three months. Significant insights on trip volume, trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have examined the steps necessary to promote economic development through RCT activities, focusing on the impact of transportation activities on the economy and emission reduction; however, there are still some problems in understanding the transportation rules. Although big data have been widely used in the field of urban transportation ( 44 , 45 ), statistical data continue to be the most commonly used data in railway container transport research. Compared with statistical data, the railway container loading and unloading station data used in this study have finer granularity and higher accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have examined the steps necessary to promote economic development through RCT activities, focusing on the impact of transportation activities on the economy and emission reduction; however, there are still some problems in understanding the transportation rules. Although big data have been widely used in the field of urban transportation ( 44 , 45 ), statistical data continue to be the most commonly used data in railway container transport research. Compared with statistical data, the railway container loading and unloading station data used in this study have finer granularity and higher accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with traditional data, big data not only has the advantages of wider sampling range and faster collection speed [47], but it has also been found that there is a strong perceived fit between big data and the urban internal structure [48,49]. At present, there are three kinds of spatial location big data that are widely used in studies related to urban space, including POI data [50], cellular signaling data and population migration data [51,52].…”
Section: Introductionmentioning
confidence: 99%